Meningkatkan Kesadaran tentang Jajanan Sehat untuk Kesehatan Anak di TK Wadi Fatimah - Marwati Marwati; Nisa Adyaningsih; Abdul Azis Romadhona; Vika Aulia Pratiska; Nabilla Larasyati; Muhammad Faishal Ghani; Fery Rizky Maulana; Intan Ayu Maharani Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This activity aims to increase awareness of children, parents, and teachers about the importance of choosing healthy snacks for the health and development of children at Wadi Fatimah Kindergarten.. The counseling program involved 73 children and utilized interactive methods such as PowerPoint presentations, educational animated videos, food replicas, group discussions, and practical simulations. The results showed a significant increase in children's understanding of healthy snacks, from 35% to 82%, as well as increased parental and teacher involvement in guiding snack choices. The methods used proved effective in creating an engaging and meaningful learning experience. This study recommends periodic evaluations and further collaboration to sustain long-term impacts.